PERBANDINGAN PENDEKATAN KOMUNIKASI VISUAL POSTER KAMPANYE PASANGAN CALON PRESIDEN DAN WAKIL PRESIDEN PEMILU TAHUN 2024: COMPARISON OF VISUAL COMMUNICATION APPROACHES IN CAMPAIGN POSTERS OF PRESIDENTIAL AND VICE PRESIDENTIAL CANDIDATES FOR THE 2024 ELECTION - Elda Franzia Jasjfi; Ariani, Ariani; Tahalea, Silvia Amanda Aurelia; Rizali, Awang Eka Novia; Kurniawan, Izzabilla Rahma Putri (Fakultas Seni Rupa dan Desain, Universitas Trisakti, 2024)
For the 2024 General Election (Pemilu) which will take place on February 14, 2024, the three pairs of President and Vice President Candidates for the 2024 Election are carrying out a campaign by distributing posters in various locations and media. These posters use various visual communication approaches, which can be examined in more depth in how the visual aspects and visual communication in them reproduce to form an image representing the identity of candidate pairs, and how the visual approaches used by the three pairs of President and Vice President Candidates in the 2024 Election compare. This research aims to describe the visual variety of posters for candidate pairs and to describe a comparison of the visual communication approaches for the posters of the three pairs of President and Vice President Candidates in the 2024 Election. This research uses qualitative methods. The data collection method was direct visual observation in Jakarta, documented using photography methods, while visual observation via the internet and social media was then documented using screenshot techniques. The visual objects used as poster model samples were selected using purposive sampling, namely with the aim of the diversity of visual communication approaches used on posters. The analysis was carried out in 2 (two) stages, the first was an analysis of the visual elements of each poster model based on the sequence of President and Vice President Candidate Numbers that had been determined by the General Election Commission of the Republic of Indonesia, and the second was a comparative analysis of the visual communication approaches carried out by each -each candidate. The results of this research are a comparative description of the visual communication approaches for the posters of the three President and Vice President Candidates which represent the figure of the candidate pair in the 2024 Election.